Manajemen Mutu Jaringan Internet di Masa Work From Home - Pwk, Dennis Saputra; Cahyadi, Eko Ruddy; Slamet, Alim Setiawan (Jurnal Manajemen, 2022)
This study aims to analyze the quality of the internet network during the Work From Home (WFH) period at cellular company. The methodology used in this research is pareto chart, fishbone analysis and comparative test analysis. This research was conducted in the period from December 2019 to November 2020. The variable used in this research is number of complaint, speed, jitter, packet loss and delay. The results of the analysis showed that there was an increase in the number of complaints after the WFH period. In addition, the comparative test showed that packet-loss, delay, jitter and complaints each showed a significant difference between before and after WFH. Otherwise, speed doesn’t showed a significant difference between before and after WFH. The implication of this research is cellular company must focus on packet loss, delay, jitter and complaints after WFH because it will affected on quality of internet connection.